1982
DOI: 10.1364/ao.21.002558
|View full text |Cite
|
Sign up to set email alerts
|

Displacement fields (U,W) obtained simultaneously by moiré interferometry

Abstract: A high-frequency phase grating on a specimen surface is illuminated symmetrically by two oblique beams.The diffracted beams emerge with wave front warpages that define both the in-plane U and out-of-plane W displacement fields. Contour maps of these wave fronts, with added carrier fringes, are obtained as a single photographic record. They are manipulated by moir6 and optical filtering steps to yield whole-field fringe patterns of U and W. Sensitivities of 0.833 ,um/fringe (32.8 ,in./fringe) for in-plane displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…A collimated laser beam illuminates a transmission grating at an angle a such that sina=X,f, (1) where X is the wavelength of the illuminating light and f is the frequency of the grating. Thus, the displacement w can be simply calculated from the interference fringe order N: w=-N, N=O,±1,±2,... (2) It is noted that the sensitivity of the measurement is independent of the frequency of the grating. A specimen that has a mirrorlike surface is placed behind the grating and is positioned in such a way that the transmitted diffraction beam TD impinges on the specimen along its normal direction.…”
Section: Description Of Methodologymentioning
confidence: 99%
“…A collimated laser beam illuminates a transmission grating at an angle a such that sina=X,f, (1) where X is the wavelength of the illuminating light and f is the frequency of the grating. Thus, the displacement w can be simply calculated from the interference fringe order N: w=-N, N=O,±1,±2,... (2) It is noted that the sensitivity of the measurement is independent of the frequency of the grating. A specimen that has a mirrorlike surface is placed behind the grating and is positioned in such a way that the transmitted diffraction beam TD impinges on the specimen along its normal direction.…”
Section: Description Of Methodologymentioning
confidence: 99%
“…The plane reference light transmits vertical the specimen grating. The information of the specimen deformations can be recorded in the holographical plates using double-exposure method, and the in-plane and the out-of-plane displacement field can be separated by filtering [4]. In this program it can be implemented to measure the in-plane and the out-of-plane displacement field synchronously, but the process of filtering is much implicated and is hard to use in the practicable measurement.…”
Section: Introductionmentioning
confidence: 99%
“…In the few cases where this has been accomplished, there were some disadvantages. Basehore and Post, 3,4 for example, proposed a technique whereby the u and w displacements were recorded together but their approach was complex in that successive optical filtering was required to separate the displacement components. Asundi et al 5 and Asundi and Cheung, 6,7 reported on an approach for simultaneous measurement of u, v, and w; however, the images recorded for in-plane and out-of-plane displacements were recorded from different positions with different magnifications.…”
Section: Introductionmentioning
confidence: 99%